2002
DOI: 10.1021/jp014259v
|View full text |Cite
|
Sign up to set email alerts
|

Visible to Infrared Luminescence from a 28-Atom Gold Cluster

Abstract: The luminescence properties of chemically prepared gold nanoclusters, each composed of a 28-atom core and a glutathione (GSH) adsorbate layer consisting of 16 molecules, were investigated. These clusters show a distinct absorption onset at 1.3 eV corresponding to the opening of an electronic gap within the conduction band (HOMO-LUMO gap). Here we report on the radiative properties of these molecular-like gold clusters. By using a combination of different detectors with sensitivities in the visible to the infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
622
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 543 publications
(672 citation statements)
references
References 33 publications
(67 reference statements)
40
622
2
Order By: Relevance
“…The total quantum yield of the luminescence as measured at ambient temperature is approximated to be about 3.5 ± 1.0 * 10 -3 with a lifetime in the microsecond range. Because of the unusually high luminescence quantum yield for a metallic cluster, it was suggested that the short-and long-wavelength luminescence bands could be assigned to the fluorescence and phosphorescence from excited singlet and triplet states, respectively, in analogy to the photophysical properties of a molecule (122). Femtosecond transient absorption studies (123) (see Figure 5a) further showed an induced transient absorption instead of a plasmon band bleach with a double-exponential decay that is independent of the laser pump power.…”
Section: Transition Between Collective Electronic Properties and The mentioning
confidence: 99%
“…The total quantum yield of the luminescence as measured at ambient temperature is approximated to be about 3.5 ± 1.0 * 10 -3 with a lifetime in the microsecond range. Because of the unusually high luminescence quantum yield for a metallic cluster, it was suggested that the short-and long-wavelength luminescence bands could be assigned to the fluorescence and phosphorescence from excited singlet and triplet states, respectively, in analogy to the photophysical properties of a molecule (122). Femtosecond transient absorption studies (123) (see Figure 5a) further showed an induced transient absorption instead of a plasmon band bleach with a double-exponential decay that is independent of the laser pump power.…”
Section: Transition Between Collective Electronic Properties and The mentioning
confidence: 99%
“…[2][3][4][5][6][7] As a result, sub-nanometer-sized metal clusters (nanoclusters) consisting of several tens of atoms are likely to exhibit molecule-like behaviors, including discrete electronic states and size-dependent fluorescence.…”
mentioning
confidence: 99%
“…GSH-stabilized AuNCs with 600 or 800 nm emission could be obtained by controlling the ratios of GSH and HAuCl 4 [36]. The Au 28 (SG) 16 cluster with quantum yield in the order of 10 -3 was obtained via reducing Au 3? in the presence of GSH with sodium borohydride (NaBH 4 ) as reducing agent [38]. Zhang and coworkers developed a facile one-step synthesis method of fluorescent GSH-AuNCs [39].…”
Section: Thiosmentioning
confidence: 99%